Transcriptomic changes in relation to early-life events in the gilthead sea bream (Sparus aurata). (December 2016) - Sarropoulou, E.; Tsalafouta, A.; Sundaram, A.; Gilfillan, G.; Kotoulas, G.; Papandroulakis, N.; Pavlidis, M.
Abstract Background Teleosts are exposed to a broad range of external stimuli, which may be either of acute or chronic nature. The larval phase of certain fish species offer a unique opportunity to study the interactions between genes and environmental factors during early life. The present study investigates the effects of early-life events, applied at different time points of early ontogeny (first feeding, flexion and development of all fins;Phase 1 ) as well as on the subsequent juvenile stage after the application of an additional acute stressor (Phase 2 ) in the gilthead sea bream (Sparus aurata ), a commercially important European aquaculture species. Animal performance, the cortisol response and gene expression patterns during early development as well as on the subsequent phases (juveniles) after the application of additional acute stressors were investigated. Results Significant differences on fish performance were found only for juveniles exposed to early-life events at the phase of the formation of all fins. On the transcriptome level distinct expression patterns were obtained for larvae as well as for juveniles with the most divergent expression pattern found to be again at the phase of the development of all fins, which showed to have also an impact later on in the acute stress response of juveniles. Conclusions The present study showed that applying an early-life protocol, characterized by the unpredictable, variable and moderate intensity of the applied stimuli provides a relative realistic model to evaluate the impact of daily aquaculture practices on fish performance. In addition, the power of investigating global gene expression patterns is shown, providing significant insights regarding the response of early-life events during development and as juveniles after the application of extra acute stressors.